A preliminary investigation on the relationships between upwelling and commercial hake fishery in the Southern Benguela - Memela, Nkuleleko (Department of Oceanography, 2021)
The hake bottom trawl division is the largest component of the fishing industry in South Africa and it is one of the strong pillars of the food industry and the national economy. It is the main source of livelihood for many people in the West Coast and as such, finding ways of advancing it towards the direction of fourth industrial revolution is at the top of societal interests and a top priority for the major companies that are key players in the industry. Sea Harvest Group Limited is one of these key players and as such, it has undertaken to be a part of the study to improve predictability of fishing by collecting data which will contribute towards the scientific study of the patterns which determine the viability of some fishing locations over the others at different times under various conditions. The studied region is the West Coast grounds located in the southern Benguela at grid (32°S: 34°S, 16°E :19°E). The study is based on the hypothesis that the main driver of the availability of hake is the upwelling, separated into its coastal Ekman transport and curl-driven components. These two components of upwelling are driven by winds and they are known to stimulate primary production and support a larger marine food web. The correlations between these upwelling types and the mean monthly catch per unit effort (CPUE) of this region is assessed. The relationship between chlorophyll abundance and hake CPUE hypothesises lagged association of hake abundance to the underlying biological food chain driven by the upwelling events. A multiple regression model is then produced as a basic step towards quantification. The results suggest that Hake CPUE is lag correlated with upwelling and that some degree of predictability can be derived from the observation of combined upwelling patterns.